Quantitative Optical Coherence Tomography Angiography of Radial Peripapillary Capillaries in Glaucoma, Glaucoma Suspect, and Normal Eyes - Mammo, Zaid; Heisler, Morgan; Balaratnasingam, Chandrakumar; Lee, Sieun; Yu, Dao-Yi; Mackenzie, Paul; Schendel, Steven; Merkur, Andrew; Kirker, Andrew; Albiani, David; Navajas, Eduardo; Beg, Mirza Faisal; et al. (American journal of ophthalmology, 2016)
To evaluate the quantitative characteristics of the radial peripapillary capillary (RPC) network in glaucoma, glaucoma suspect, and normal eyes using speckle variance optical coherence tomography angiography (OCT-A). To determine correlations between RPC density, nerve fiber layer (NFL) thickness, and visual field indices. Cross-sectional study. OCT-A images of RPCs were acquired at a single institution using a custom-built 1060 nm system from 3 groups: unilateral glaucoma (10 eyes from 5 subjects), glaucoma suspects (6 eyes from 3 subjects), and normal control eyes (16 eyes from 9 normal subjects). Peripapillary NFL thickness measurements were determined using spectral-domain optical coherence tomography. Glaucoma and glaucoma suspects also underwent automated 30-2 Humphrey visual field analysis. Manual tracing techniques were used to quantify RPC density in the OCT-A images. Data were analyzed using a linear mixed model with 1 fixed-effect covariate. Correlations between main outcome measures (RPC density, NFL thickness, and visual field index) were determined. Mean age was not significantly different between the 3 groups (P = .25). The density of RPCs was significantly lower in glaucomatous eyes compared with matched-peripapillary regions in the fellow eye, glaucoma suspect group, and normal group (all P < .001). RPC density was strongly correlated with NFL thickness (P < .001) and visual field index (P < .001). Significant reductions in RPC density were correlated with sites of NFL decrease and visual field loss in glaucoma. Speckle variance OCT-A allows visualization and quantification of RPCs and may therefore be a useful tool for indirectly quantifying and monitoring retinal ganglion cell axonal injury in glaucoma.